A Chandra Study of the NGC 7618/UGC 12491 Major Group Merger at Apogee: Multiple Cold Fronts, Boxy Wings, Filaments, and Arc-shaped Slingshot Tails - Machacek, M. E.; Jones, C.; Kraft, R. P.; Forman, W. R.; Roediger, E.; Sheardown, A.; Wan, J. T. (Astrophysical Journal, 2023)
Analyses of major group mergers are key to understanding the evolution of large-scale structure in the Universe and the microphysical properties of the hot gas in these systems. We present imaging and spectral analyses of deep Chandra observations of hot gas structures formed in the major merger of the NGC 7618 and UGC 12491 galaxy groups and compare the observed hot gas morphology, temperatures, and abundances with recent simulations. The morphology of the observed multiple cold front edges and boxy wings are consistent with those expected to be formed by Kelvin-Helmholtz instabilities and gas sloshing in inviscid gas. The arc-shaped slingshot tail morphologies seen in each galaxy suggest that the dominant galaxies are near their orbital apogee after having experienced at least one core passage at a large impact parameter.
Keywords: Galaxy environments; Galaxy mergers; Cool intergalactic medium; X-ray astronomy; Galaxy groups